The effectiveness of the organ on politics defence and security in conflict transformation in Africa: case of DRC armed conflicts 2002. - Chin'anga, Juliana (Midlands State University, 2019)
The study sought to evaluate the effectiveness of the SADC Organ on Politics, Defence and Security in conflict transformation in Africa specifically looking at the case of the DRC armed conflicts and other peace threatening related cases. The study was prompted by the need for Africans to realize that togetherness and cooperation can lead to development in the region. This research was accomplished through qualitative methods of data collection and analysis, namely e-mailed questionnaire, face to face interviews and in-depth interviews. Findings from this research reveal that the SADC Organ on Politics, Defence and Security has played a fundamental role in bringing the social and political achievements in the SADC region Security has greatly improved. However despite the achievements, findings also reveal that the SADC Organ has been mostly active within the region it is located and most of its achievements has been through the help of the AU and UN. The findings have also indicated that the Organ’s major challenge is that of inadequate funding to increase equipment and human resources this has been a setback for the Organ to carry out operations on its own without the intervention of other bigger Organisations and this has resulted in the Organ being given less credit on the operations they participated in. In light of the setbacks and challenges encountered by the Organ several recommendations have been proffered for the SADC Organ on Politics, Defence and Security to ensure sustainable peace, security and political development in Africa.